2015
DOI: 10.1111/acer.12646
|View full text |Cite
|
Sign up to set email alerts
|

Visceral White Adipose Tissue is Susceptible to Alcohol-Induced Lipodystrophy in Rats: Role of Acetaldehyde

Abstract: Background Chronic alcohol exposure causes lipid dyshomeostasis at the adipose-liver axis, reducing lipid storage in white fat and increasing lipid deposit in the liver. Previous studies have shown that visceral fat, rather than subcutaneous fat, is a risk factor for metabolic diseases. This study was conducted to determine whether chronic alcohol exposure differentially affects lipid metabolism in visceral (epididymal) and subcutaneous fat, and the mechanisms underlying the alcohol effects. Methods Male Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 41 publications
3
53
0
Order By: Relevance
“…In vitro experiment on 3T3-L1 with alcohol revealed an overexpression for CYP2E1, decreased adiponectin secretion similar to in vivo experiment in rat [61]. In another experiment, 3T3 L1 adipocytes with acetaldehyde resulted in decrease lipogenic regulators like PPAR γ, lipid [67].…”
Section: Adipose Tissue and Alcoholsupporting
confidence: 65%
See 2 more Smart Citations
“…In vitro experiment on 3T3-L1 with alcohol revealed an overexpression for CYP2E1, decreased adiponectin secretion similar to in vivo experiment in rat [61]. In another experiment, 3T3 L1 adipocytes with acetaldehyde resulted in decrease lipogenic regulators like PPAR γ, lipid [67].…”
Section: Adipose Tissue and Alcoholsupporting
confidence: 65%
“…A study demonstrated that chronic alcohol exposure enhances WAT lipolysis in association with activation of major adipose triglyceride hydrolases [72]. CYP2E1 is also expressed in adipose tissue, thus up regulation of CYP2E1 on alcohol consumption leads to oxidative stress and affect the metabolism [67]. In vitro experiment on 3T3-L1 with alcohol revealed an overexpression for CYP2E1, decreased adiponectin secretion similar to in vivo experiment in rat [61].…”
Section: Adipose Tissue and Alcoholmentioning
confidence: 80%
See 1 more Smart Citation
“…Consistent with their findings that alcohol suppresses lipolysis via the β-AR pathway [39,40], Kang et al, 2006 found that alcohol decreases HSL Ser660 phosphorylation [39]. Only one other investigation has reported a similar decrease in eWAT from rats after 12 weeks of an alcohol-containing liquid diet [19]. Instead, the majority of work shows HSL phosphorylation, activity or mRNA to be increased [7,9,11,12,14,15,18,45,46] or at least unchanged by alcohol [7,14,18,45].…”
Section: Regulation Of Lipid Balancementioning
confidence: 65%
“…In contrast, chronic alcohol feeding in rats does not consistently increase fat mass potentially due to improper pair-feeding techniques [16,17], differences in macronutrient composition of the diets (i.e., high fat versus low fat), doses of alcohol used, feeding methods (liquid diet, in water, through gastric tube), or the interaction of these methodological variances in the different adipose tissue depots (eWAT vs. sWAT). Of those animals receiving alcohol as part of a complete nutritionally adequate liquid diet, visceral and subcutaneous adipose tissue mass was unchanged [18,19], while eWAT was either unchanged [20] or decreased [19,21]. A high dose of alcohol (5 g/kg/day) administered via a gastric tube to animals consuming a low fat (10%) chow diet increased eWAT and perirenal depots [22].…”
Section: Chronic Alcohol and Adipose Tissue Massmentioning
confidence: 99%